Workplace primary prevention programmes enabled by information and communication technology - Fatemeh Nikayin; Marikka Heikkilä; Mark de Reuver; Sam Solaimani (Elsevier Inc., 2022)
As the workforce is ageing across the globe, employers are implementing primary prevention programmes to encourage their employees to live healthier lives. Information and communication technology (ICT) can support these programmes by collecting, storing and processing data, and by visualizing health progress. However, there is a lack of knowledge of how ICT is utilized in primary prevention programmes at workplaces and how its utilization affects social issues. This paper fills that gap by presenting an illustrative case of a primary prevention programme in Finland. We find that offering employees the opportunity to use ICT for data collection, storage and sharing, contributes to their acceptance of the programme. Moreover, our findings show that while visualizing the effects of the programme through ICT contributes to lifestyle change, such soft factors as the involvement of doctors are just as important.